Normative social influence on meat consumption - Laura Einhorn (Max Planck Institute for the Study of Societies, 2020)
Studies from various disciplines show that including more meat-free dishes in our diets benefits our environment and our health while also promoting animal welfare. However, little is known about what encourages the adoption of more meat-free meal choices into our everyday diets. This paper focuses on the role of normative social influence on food choice as a potential answer to this question. In a real-world setting and based on the combination of a field and a survey experiment in seven German university dining halls, I analyze the impact of social norms on meat consumption in a single meal choice situation. I distinguish between descriptive and injunctive norms as well as between remote and direct norms. In a first step, descriptive and injunctive remote norm message interventions promoting a vegetarian diet were implemented. In a second step, the influence of direct social norms, i.e., the influence of vegetarian peers on non-vegetarians' meal choice, was assessed. I find that neither type of remote eating norm influences food choice, while direct normative influence leads to convergence towards vegetarian meal choices in a university setting. I summarize the implications of these findings, discuss their limitations, and point to directions for future research. – – Studien unterschiedlicher Fachdisziplinen betonen, dass sich eine fleischreduzierte Ernährungsweise positiv auf Umwelt, Tierwohl und auf die menschliche Gesundheit auswirken kann. Wir wissen dennoch wenig darüber, welche Faktoren eine solche Ernährungsweise begünstigen. Dieser Beitrag untersucht den Einfluss sozialer Normen als mögliche Antwort auf diese Frage. Basierend auf einem Feldexperiment und einer Umfrage in sieben deutschen Hochschulmensen wird analysiert, wie sich Ernährungsnormen auf die Entscheidung für oder gegen ein fleischloses Gericht auswirken. Es wird dabei sowohl zwischen deskriptiven und präskriptiven als auch zwischen direkten und indirekten pro-vegetarischen Ernährungsnormen unterschieden. Im ersten Schritt werden pro-vegetarische Normen durch experimentelle Interventionen implementiert. Im zweiten Schritt wird der Einfluss von Vegetarierinnen und Vegetariern auf die Menüwahl nicht vegetarisch lebender Menschen analysiert. Während die experimentellen Interventionen keinen Einfluss auf die Menüwahl der Mensagäste haben, passen sich Nicht-Vegetarierinnen und -vegetarier im studentischen Umfeld bei der Menüwahl tendenziell den vegetarisch essenden Mitgliedern einer Tischgemeinschaft an. Die Ergebnisse, Einschränkungen sowie die Implikationen dieser Studie für weitere Forschung werden abschließend diskutiert.
hdl:21.11116/0000-0005-C748-A
Keywords: 300; descriptive norms; field experiment; food choice; injunctive norms; meat consumption; social influence; vegetarianism; deskriptive Normen; Ernährung; Feldexperiment; Fleischkonsum; präskriptive Normen; soziale Normen; Vegetarismus